Factors Associated with Road Traffic Accidents in Kathmandu, Nepal: A Cross-Sectional Study - Rajesh Karki; Bhawana Pudashaini; Sanjaya Kumar Shah (Shahid Sadoughi University of Medical Sciences, 2023)
Background: Road traffic accidents (RTAs) are a leading and disproportionately prevalent cause of mortality and disability, particularly burdening Nepal, primarily within the Kathmandu Valley. Methods: This cross-sectional study was conducted between March 22nd and April 24th, 2021, involving 185 victims admitted to the emergency department of a private hospital. Respondents were selected using purposive sampling, and data were collected through face-to-face interviews. Socio-demographic characteristics, human factors, and environmental factors data were analyzed using descriptive statistics, and all statistical tests were conducted using SPSS version 20. Results: Among the 185 RTA victims, the majority (36.8%) fell within the 21-30 age groups. Male victims (55.7%) outnumbered females (44.3%). Students (36.8%) experienced the highest accident rates, with most incidents (21.1%) occurring on Saturdays and 38.4% taking place between 12:00pm and 6:00pm. Human Factors and RTA: Of the total victims, 80 (43.2%) were drivers, with 43.75% of them reporting the use of emergency brakes. Furthermore, 77.61% indicated that accidents were caused by pedestrians not using zebra crossings when crossing the road. Environmental Factors and RTA: Rainy weather was associated with the highest number of accidents, accounting for 36.2% of cases. Additionally, narrow routes (28.6%) and slippery roads (25.9%) contributed to a significant number of accidents. Conclusion: Nepal faces a high rate of road traffic accidents, with critical factors including victim age, vehicle types, speed, road and weather conditions, and traffic rule violations. Authorities must consider these factors to effectively control and prevent RTAs. Corresponding Author: Rajesh Karki View Orcid in Profile You can search for this author in PubMed & Google Scholar Profile